Knowledge, Attitude and Practice of Postnatal Mothers for Early Initiation of Breast Feeding in The Obstetric Wards of a Tertiary Care Hospital of Vadodara City - Shwetal Bhatt; Pooja Parikh; Neha Kantharia; Amit Dahat; Rahul Parmar (Medsci Publications, 2012)
Background: Despite its known advantages, breastfeeding rates are low world over. Large number of factors affects breastfeeding. The aim was to study maternal and neonatal factors that affect early initiation of breastfeeding in the perinatal period and to evaluate the knowledge, attitude and practice of postnatal mothers for early initiation of breast feeding in the obstetric wards. Methods: A cross sectional study carried out from October 2010 to December 2010. Study conducted in 175 Post natal mothers from the maternity wards of a tertiary care hospital in Vadodara city. Mothers were interviewed within 5 days after the birth of the child. Data was collected using a structured questionnaire with some open and close ended questions and data was analyzed by Epi Info 3.2 (window based) software. Results: Most common causes of delay in initiating breastfeeding were caesarian section and fatigue (29.7% and 21.1% respectively). 32.6% mothers initiated breastfeeding within one hour of delivery. Incidence of early initiation of breastfeeding in mothers less than 21 years of age was 29.4%, 24.6% in illiterate mothers and 25% in those delivering by caesarian section. Early initiation of breastfeeding was maximum (46.7%) in the first and minimum (24.3%) in the third shift of work of health care workers. Conclusion: Lack of adequate information, maternal education level, socioeconomic factors, etc. influences the early breast feeding practices which can be overcome by proper support, care and counseling provided by health care staff.